Net primary production of forest-forming species in climatic gradients of Eurasia - V. A. Usoltsev; K. V. Kolchin; V. P. Chasovskikh (Сибирский лесной журнал, 2018)
When using biomass and net primary production (NPP) databases compiled by the authors for 6 forest-forming species in a number of 6694 and 2192 sample plots correspondingly, a system of regression models of their NPP is designed and some species-specific regularities of NPP distribution in two climatic gradients (natural zonality and climate continentality) are stated. It is found that according to a zonal gradient, aboveground and total NPP in 2-needled pine and spruce-fir forests are monotonically increasing in the direction from the northern to the southern tip of the continent, while larch and birch have the maximum in the southern moderate, and aspen and poplar – in the northern moderate zone, but oak forests do not show any significant pattern. Within a single zonal belt, the aboveground and total NPP of coniferous and deciduous are monotonically decreasing in direction from the Atlantic and Pacific coasts to the continentality pole in Yakutia. The understory NPP of all the species, except oak, monotonically increase towards the subequatorial zone. For oak forests, any clear regularity is not revealed. Within a single zonal belt, when approaching continentality pole, Pinus and Quercus NPP monotonically decreases and in other species, increases. Species-specific patterns in changing the relative indices of NPP (forest stand underground NPP to aboveground one and forest understory NPP to total forest stand one) in gradients of the natural zonality and climate continentality are established.